Reconsidering Urate-Lowering Therapy in Chronic Kidney Disease- Guideline Driven Perspectives on the Management of Asymptomatic Hyperuricaemia - Sourabh Sharma,; Sabine Karam,; Intissar Haddiya,; Sanjay Kalra, (Journal of the Pakistan Medical Association, 2026)
Hyperuricaemia is highly prevalent in patients with chronic kidney disease (CKD), primarily due to reduced renal urate excretion. Elevated serum uric acid (SUA) levels have been linked with CKD progression, cardiovascular disease, and mortality. However, association does not imply causation. Over the last decade, multiple studies have failed to demonstrate a renoprotective or cardiovascular benefit of urate-lowering therapy (ULT) in patients with asymptomatic hyperuricaemia. Consequently, major international societies, including Kidney Disease: Improving Global Outcomes (KDIGO), the American College of Rheumatology (ACR), and the European Alliance of Associations for Rheumatology (EULAR), recommend against pharmacologic treatment of asymptomatic hyperuricaemia, including in patients with CKD. This review synthesizes current guideline recommendations, randomized clinical trial evidence, and practical clinical considerations to delineate scenarios in which ULT should not be initiated in patients with chronic kidney disease, while highlighting the importance of supportive and nonpharmacologic management strategies. Keywords: Hyperuricaemia, Chronic kidney disease, Asymptomatic hyperuricaemia, Urate-lowering therapy, Allopurinol, Febuxostat, Gout